Language and Identity: Exploring the Relationship between Language Use and Cultural Identity among Bilingual Speakers - Baharuddin Purba; Milisi Sembiring; Dafid Timotius Nduru; Ictiar Telaumbanua; Affan Lubis; Ilham Al Khairi (Jurnal Ilmu Sosial Mamangan, 2024)
This research was conducted to describe the relationship between language and culture from a bilingual perspective. From a perspective, the theoretical framework is based on several factors, which are related beyond language itself. It has a relationship with the community of speakers of the language. This research uses the literature study method as material to determine the relationship between language and culture from the perspective of bilingual users. From this point of view, theories that describe the correlation between culture and language have 2 categories consisting of subordinate relevance and also theories of coordinative relevance. The first relationship is correlated with the view that culture is a primary system. While language is a subsystem. Meanwhile, the second relationship has an understanding that language and culture are two different systems, which are adhered to by humans. Culture is a system that regulates the process of human interaction. Meanwhile, language is a system that is a tool for interaction for bilinguals.